Arsitektur Biomorfik: Kura-Kura Ocean Park Sebagai Landmark Wisata Jepara - Hikmal Adiyatma Putra (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The purpose of writing this article is to provide knowledge to the public about the Biomorphic Architecture of the Turtle Ocean Park building in Jepara, Central Java. This research uses qualitative methods, namely observation and literacy. The results of this study explain that the Kura-Kura Ocean Park Jepara building is a building that has a biomorphic architectural style. Biomorphic architecture is a style of harmonious concept between buildings and the environment or nature. Kura-Kura Ocean Park is a center for recreation and interaction with marine biota which has educational value to the community.